Modeling of cloud system using Erlang formulas - Firdhous, Mohamed; Ghazali, Osman; Hassan, Suhaidi (2011)
Cloud computing has been considered as the 5th utility after electricity, water, gas and telephony.When the cloud computing matures, there will be multiple vendors offering different services at different Quality of Services and at different prices.This would necessitate new tools and mechanisms for analyzing the performance of the system for matching the offerings with requirements. In this paper the authors have modeled the cloud system using queuing theory, specifically Erlang formulas.Four different cloud utility models of various complexities have been presented and analyzed using simulations.The simulations results have also been presented along with an in depth discussion.